Moringa oleifera leaf extract influences oxidative metabolism in C2C12 myotubes through SIRT1-PPARα pathway - Guglielmo Duranti; Mariateresa Maldini; Domenico Crognale; Stefania Sabatini; Federica Corana; Katy Horner; Roberta Ceci (Elsevier, 2021)
Background: Moringa oleifera is an important traditional multipurpose plant, due to the presence of many bioactive compounds. Moringa oleifera leaf extracts (MOLE) have been shown to have many beneficial properties in pathological conditions including diabete. However, the lack of information about its exact molecular mechanism of action might hinder other potential use in different areas such as skeletal muscle physiology. Hypothesis/purpose: Skeletal muscle represents about 40-50% of the total mass of a lean individual and is an insulin-sensitive tissue with wide variations in energy requirements. We aimed to test the effects of MOLE on oxidative metabolism and the molecular mechanism involved on myotubes by using C2C12 cell line, a well known model for in vitro skeletal muscle studies. Study design: C2C12 myotubes were treated with MOLE at different working solutions for 24 and 48 hours and then culture media and cellular extracts were collected. MOLE was screened for phytochemicals determination. Methods: Glucose and free fatty acids consumption along with lactate release were assessed in the culture media. Citrate sinthase, 3-hydroxy acylCoA dehydrogenase, alanine transglutaminase and creatine kinase enzyme activities, as well as the metabolic regulatory SIRT1 and PPARα protein levels were evaluated in cellular extracts. Results: MOLE administration induced a dose and time dependent increase in substrates consumption accompanied by an increase in intracellular oxidative metabolism enzymatic activity levels. The extracts were also able to modulate positively the protein expression of SIRT1 and PPARα. Conclusion: Altogether, these data indicate that MOLE could represent a valid nutritional support for improving skeletal muscle metabolism: in fact MOLE treatment increased oxidative energy metabolism and possibly favours mitochondrial biogenesis through SIRT1/PPARα pathway. future studies will clarify wether Moringa oleifera leaf extracts consumption may be useful to improve physical performance and metabolic-related skeletal muscle diseases.